2020
DOI: 10.21203/rs.3.rs-97866/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

C1QBP regulates apoptosis of renal cell carcinoma via modulating xanthine dehydrogenase (XDH) mediated ROS generation

Abstract: Background Complement component 1 Q subcomponent binding protein (C1QBP) is a multifunctional protein and plays a vital role in the progression and metabolism of cancer. Our previous study has revealed that the low expression of C1QBP in renal cell carcinoma (RCC) and knockdown of C1QBP promotes the adhesion and invasion of RCC cells. However, its functions in the metabolism, oxidative stress and apoptosis of RCC cells have not yet been explored. Methods Metabolomics assay was applied to investigate the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Consistent with our ndings, several studies reported that XO activity was decreased in a number of cancers, such as colon cancer [39], kidney and bladder [40]. In addition, low XO expression was correlated with more aggressive cancers [41], indicating that XO plays an important role in cancer progression and may become a risk factor [42]. The decrease in XO activity might provide an advantage to the cancer cells by reducing the generation of ROS, which may induce the apoptosis pathway and cell death.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our ndings, several studies reported that XO activity was decreased in a number of cancers, such as colon cancer [39], kidney and bladder [40]. In addition, low XO expression was correlated with more aggressive cancers [41], indicating that XO plays an important role in cancer progression and may become a risk factor [42]. The decrease in XO activity might provide an advantage to the cancer cells by reducing the generation of ROS, which may induce the apoptosis pathway and cell death.…”
Section: Discussionsupporting
confidence: 91%
“…During salvage purine metabolism, hypoxanthine can be either recycled to inosine monophosphate (IMP) by HPRT or synthesized by deamination of adenosine by adenosine deaminase (ADA) to produce inosine; inosine will be converted to hypoxanthine by purine nucleoside phosphorylase (PNP) [33]. Later, during the purine catabolism pathway, hypoxanthine will be converted to xanthine then to uric acid by xanthine oxidase.Reactive oxygen species (ROS) will be produced as a by-product of the catabolism pathway [42]. The increasing level of intracellular ROS is postulated to induce apoptosis and cancer cell death.…”
Section: Discussionmentioning
confidence: 99%